A Long-Term, Open-Label Study to Evaluate the Safety and Tolerability of Brexpiprazole as Adjunctive Therapy in Adults With Major Depressive Disorder. Issue 3 (May 2019) - Hobart, Mary; Zhang, Peter; Skuban, Aleksandar; Brewer, Claudette; Hefting, Nanco; Sanchez, Raymond; McQuade, Robert D.
Abstract: Background: Long-term treatment is recommended in major depressive disorder (MDD) to prevent relapse and to restore functioning. The aim of this study (Orion; NCT01360866) was to assess the long-term safety, tolerability, and efficacy of open-label treatment with adjunctive brexpiprazole in adult patients with MDD. Methods: Patients rolled over into this 52-week study (amended to 26 weeks) from 3 randomized, double-blind, placebo-controlled studies. Patients received brexpiprazole 0.5 to 3 mg/d (flexible dose) adjunct to their current antidepressant treatment. The primary outcome variable was the frequency and severity of treatment-emergent adverse events (TEAEs). Efficacy was assessed as a secondary objective using clinical rating scales. Results: A total of 2944 patients were enrolled (1547 for 52 weeks, 1397 for 26 weeks), of whom 1895 (64.4%) completed the study. The TEAEs with incidence of 5% or greater were weight increase (17.7%), somnolence (8.0%), headache (7.2%), akathisia (6.7%), increased appetite (6.3%), insomnia (6.3%), fatigue (6.1%), viral upper respiratory tract infection (5.4%), and anxiety (5.2%). Most TEAEs were mild or moderate in severity. The mean increase in body weight was 2.7 kg to week 26 and 3.2 kg to week 52; 25.8% of patients had a weight increase of 7% or greater at any postbaseline visit. There were no clinically relevant findings related to extrapyramidal symptoms, prolactin, lipids, or glucose. Patients' symptoms and functioning showed continual improvement. Conclusions: Adjunctive treatment with open-label brexpiprazole 0.5 to 3 mg/d was generally well tolerated for up to 52 weeks in patients with MDD and was associated with continued improvement in efficacy measures and functional outcomes. Abstract : Supplemental digital content is available in the text.